Theoretical and Experimental Study of Bonding and Optical Properties of Self-Assembly Metallophthalocyanines Complexes on a Gold Surface. a Survey of the Substrate-Surface Interaction - Zagal-Moya, J; Zagal-Moya, J; Silva-Rojas, J; Silva-Rojas, J; Ponce-Hormazabal, I; Onate, R (2011)
The formation of self-assembly monolayers (SAMs) based on a gold substrate and a thiolate ligand as "anchor" fragment of metallophtalocyanine has been employed as strategy toward the obtention of modified electrodes. In this Article, the formation of SAMs involving iron and cobalt phtalocyanines anchored by 4-aminothiophenol (4-ATP) and 4-mercatopyridine (4-MP) to the Au(111) surface is explored by both experimental and theoretical studies for a better understanding of their bonding pattern and optical properties. The self-assembly metallophthalocyanines complexes on gold electrode exhibits an interesting charge donation from the 4-ATP or 4-MP toward both gold substrate and phtalocyanine, denoting an effective gold-MPc interaction mediated by the titled anchor ligands. In addition, the optical properties of the self-assembled complexes supported on the gold electrode exhibit in conjuction with the well-described Q-band an interesting charge transfer from the Pc (?) toward the gold surface, as could be observed in the FePc-4MP-Au26 assembly. © 2011 American Chemical Society.